Malnutrition in Children with Chronic Diarrhea During Early Childhood at A Tertiary Care Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Background: There is a two way relationship between disease and malnutrition. The consequences of malnutrition during formative early years can extend long beyond the disease itself, necessitating the interception of this continuous cycle.Objective: To assess the nutritional status of children having chronic diarrheaMaterials and Methods: The study was a cross–sectional survey. A purposive sample of 50 chronic diarrhea patients between 1-3 years of age was collected from pediatric outdoor patient department, Sir Ganga Ram Hospital, Lahore. Anthropometric data (height and weight) was compared to the reference population in terms of key malnutrition indices. The data was then analyzed for the frequency as well as severity of malnutrition in the study sample.Results: Sixty eight percent of the sample was found to be underweight, 56% wasted and 64% stunted. The proportion of severely malnourished individuals (
Keywords: Chronic diarrhea, frequent infections, severe malnutrition, malnourished children